2020
DOI: 10.3389/fimmu.2020.574593
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever and COVID-19: Friends or Foes?

Abstract: Familial Mediterranean Fever (FMF) and COVID-19 show a remarkable overlap of clinical symptoms and similar laboratory findings. Both are characterized by fever, abdominal/chest pain, elevation of C-reactive protein, and leukocytosis. In addition, colchicine and IL-1 inhibitors treatments that are effective in controlling inflammation in FMF patients have recently been proposed for off-label use in COVID-19 patients. Thus, FMF may resemble a milder recapitulation of the cytokine storm that is a hallmark of COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Activation of inflammasomes by viral proteins and release of proinflammatory cytokines is a natural response of innate immunity to viral infections however, a dysregulated inflammasome activity may also result in an aberrant inflammatory response. Likewise, in Familial Mediterranean fever (FMF), a hereditary innate immunity disorder due to gain of function mutations in Mediterranean fever gene ( MEFV) encoding pyrin protein, a hyperactive pyrin inflammasome leads to febrile inflammatory episodes sharing similarities with COVID-19-associated cytokine storm [ 4 , 5 ]. As mentioned before, an already hyperresponsive innate immune system may increase susceptibility developing cytokine storm and severe symptoms in COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of inflammasomes by viral proteins and release of proinflammatory cytokines is a natural response of innate immunity to viral infections however, a dysregulated inflammasome activity may also result in an aberrant inflammatory response. Likewise, in Familial Mediterranean fever (FMF), a hereditary innate immunity disorder due to gain of function mutations in Mediterranean fever gene ( MEFV) encoding pyrin protein, a hyperactive pyrin inflammasome leads to febrile inflammatory episodes sharing similarities with COVID-19-associated cytokine storm [ 4 , 5 ]. As mentioned before, an already hyperresponsive innate immune system may increase susceptibility developing cytokine storm and severe symptoms in COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the genetic variant at 9q33.1 may act in a biological pathway that is shared with that of colchicine, which acts on multiple inflammatory pathways including the NLRP3 inflammasome 33 , 34 . A recent report by Stella and colleagues 35 on familial Mediterranean Fever (FMF) in the context of COVID-19 argues that there could be a finely regulated competition between the NLRP3 inflammasome and pyrin that is necessary to maintain protective inflammation levels. FMF is an inherited monogenic autoinflammatory disorder caused by excess activity of the pyrin protein and which is typically treated with colchicine to prevent fever attacks.…”
Section: Discussionmentioning
confidence: 99%
“…The first antiviral response is initiated by the innate immune system. Secretion of type 1 interferons and proinflammatory cytokines occurs in this response [ 8 ]. The inflammatory phase may cause rapid deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that impairment in the regulation of NLRP3 inflammasome could lead to a complex immune response in viral infections [ 20 ]. Stalla et al hypothesized that the dysregulation between Pyrin and NLRP3 inflammasome might alter the balance between protective inflammation against virus and hyperinflammation [ 8 ]. Therefore, the frequency and severity of SARS-CoV-2 infection in FMF are intriguing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation